The Economic Impact of a Junior Club Sporting Event: Caravan Fans (American Journal of Management, 2021)
This study investigated the economic impact of visitor’s expenditures at a junior girl’s club sporting event in the city of Denver, Colorado. This study uses a random sample of 2,000 sport fans of which 1,163 surveys were found to be usable (n=1,163). The findings reveal that hosting a club sports national tournament can generate substantial economic benefits and, in some cases, greater than those associated with mega sporting events. Key findings are that economic impact can play a critical role in assessing the potential benefits of hosting small events and that youth sport event managers must make sure to meet the needs of caravan fans. Caravan fans are the parents and family members that attend these events to watch their children participate.
Keywords: management; youth sporting event; economic impact; caravan fan